2005
DOI: 10.1021/ja044404t
|View full text |Cite
|
Sign up to set email alerts
|

Factors Governing the Substitution of La3+ for Ca2+ and Mg2+ in Metalloproteins:  A DFT/CDM Study

Abstract: Trivalent lanthanide cations are extensively being used in biochemical experiments to probe various dication-binding sites in proteins; however, the factors governing the binding specificity of lanthanide cations for these binding sites remain unclear. Hence, we have performed systematic studies to evaluate the interactions between La3+ and model Ca2+ - and Mg2+ -binding sites using density functional theory combined with continuum dielectric methods. The calculations reveal the key factors and corresponding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
72
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 59 publications
13
72
0
Order By: Relevance
“…The geometrically predicted locations with 2-4 negatively charged ligands, strong negative surface potential, and functionally necessary residues were more likely to bind Ca 2ϩ . The model structures of CD2 variants with grafted potential Ca 2ϩ -binding sites of the CaSR were generated by SWISSMODEL (33,34 52 and Gly 53 of CD2 in the plasmid pGEX-2T (denoted as CD2-CaSR1 and CD2-CaSR2, respectively) by PCR using an established protocol (63). Two mutants, CD2-CaSR1-E228A/E229A and CD2-CaSR2-E378A/E379A, were also made by site-directed mutagenesis.…”
Section: Computational Prediction Of Camentioning
confidence: 99%
“…The geometrically predicted locations with 2-4 negatively charged ligands, strong negative surface potential, and functionally necessary residues were more likely to bind Ca 2ϩ . The model structures of CD2 variants with grafted potential Ca 2ϩ -binding sites of the CaSR were generated by SWISSMODEL (33,34 52 and Gly 53 of CD2 in the plasmid pGEX-2T (denoted as CD2-CaSR1 and CD2-CaSR2, respectively) by PCR using an established protocol (63). Two mutants, CD2-CaSR1-E228A/E229A and CD2-CaSR2-E378A/E379A, were also made by site-directed mutagenesis.…”
Section: Computational Prediction Of Camentioning
confidence: 99%
“…The ''EEEEE'' mutant appears that it will bind the 3+ metals tightly, although maybe not with much specificity. This site does satisfy recommendations made by Dudev et al [21] for reengineering sites to bind another lanthanide, La 3+ , by minimizing the solvent exposure and flexibility of the metal-binding cavity, freeing both carboxylate oxygen atoms of aspartate/glutamate side chains so they can bind bidentately in the metal-ion binding site, and maximizing the number of metal-bound carboxylate groups in buried sites. However, we do not retain an asparagine/glutamine side chain in our proposed Al 3+ -binding peptide since Al 3+ is much smaller and has a higher charge density than the lanthanides.…”
Section: Resultsmentioning
confidence: 89%
“…Soft sulfur ligands are uncommon. In systematic studies in which La 3+ replaced Ca 2+ and Mg 2+ in metalion binding sites, it was found that the La 3+ cation was favored and facilitated by minimizing the solvent exposure and flexibility of the metal-binding cavity, freeing both carboxylate oxygen atoms of aspartate/glutamate side chains so they could bind bidentately in the metal-ion binding site, maximizing the number of metal-bound carboxylate groups in buried sites, and including an asparagine/glutamine side chain in sites with four aspartate/ glutamate side chains [21]. Holding the ligand constant, the coordination is most strongly affected by the metal's size rather than its charge, especially if the ligand is neutral.…”
Section: Introductionmentioning
confidence: 99%
“…Charge transfer is highest in these conformation, which favours the attachment of trivalent cations [3]. In the most solvent exposed areas, the preferred conformation for exchange is 3M because of the polarization effect.…”
Section: Metal Exchange Reactionmentioning
confidence: 98%
“…Providing accurate metal-site structures in proteins is crucial for several studies regarding the design of drugs [1,2], metal toxicity, specificity of proteins or development of new techniques [3]. Lately, the importance of the combination of experimental and computational works has been addressed [4,5], specially when studying the structure and thermodynamics of the metal binding to a protein.…”
Section: Introductionmentioning
confidence: 99%